The Relationship between Breastfeeding and Dental Caries in Preschool Children in Saudi Arabia: A Systematic Review - Sara M Bagher; Heba J. Sabagh; Ahmed A. Mohammed; Khloud K. Baghlaf (Journal of King Abdulaziz University: Medical Sciences, 2023)
The aim of this study was to carry out a systematic review on the existing data within the literature to determine the relation between breastfeeding and caries in Saudi Arabia on preschool children. Using Cochrane search strategy, a search protocol was prepared to review all published data for this study. The search was run on March 2011 in all languages as to identify all eligible studies for our review. Eight articles met the criteria. No significant differences between children with ECC and caries free children regarding the type of feeding. Breastfeeding frequency, feeding on demand, especially during sleep, and late weaning were found to be significant factor in most of the included studies. There were limited number of studies carried out in Saudi Arabia that correlate the possible relationship between breastfeeding and dental caries in preschool children. Therefore, more rigorous investigation in a larger sample size that represents the population, after standardizing and identifying the different confounding factors is required.